2018
DOI: 10.1002/mus.26174
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological study of the radial nerve variant in the innervation of the dorsomedial surface of the hand

Abstract: It is important to know the characteristics of this variant in order to avoid diagnostic errors and to prevent iatrogenic lesions in surgery performed on the dorsum of the wrist. Muscle Nerve 58: 732-735, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
2
2
Order By: Relevance
“…In contrast to previous studies, 5‐14 an all‐radial supply to the dorsum of the hand was not found in our study. Although there are various possible reasons for the discrepancy, racial difference may be a factor.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to previous studies, 5‐14 an all‐radial supply to the dorsum of the hand was not found in our study. Although there are various possible reasons for the discrepancy, racial difference may be a factor.…”
Section: Discussioncontrasting
confidence: 99%
“…[4][5][6] Furthermore, the SBRN territories most commonly seen in our study are comparable to the sensory territory delineated by microneurography. 15 Because sensory innervation was shared by the SBRN and In contrast to previous studies, [5][6][7][8][9][10][11][12][13][14] an all-radial supply to the dorsum of the hand was not found in our study. Although there are various possible reasons for the discrepancy, racial difference may be a factor.…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations